Adverse reactions to 1% cyclopentolate eye drops in children: an analysis using logistic regression models. (10th December 2020) - Imai, Toshihiro; Hasebe, Satoshi; Furuse, Takashi; Morisawa, Shin; Hasebe, Kayoko; Nagata, Yuka; Tokutake, Tomoki; Moriyama, Yumiko
Abstract: Purpose: To determine the frequency, symptoms and risk factors for adverse reactions to two‐times instillation of 1% cyclopentolate in children. Study design: Prospective, observational study. Methods: The subjects were 646 patients who underwent cycloplegic refraction with cyclopentolate (mean age; 7.0 ± 3.5 years, age range; 0–15 years). Five minutes after instillation of 0.4% oxybuprocaine hydrochloride, a 1% cyclopentolate eye drop was instilled twice, with an interval of 10 min. Fifty minutes later, two certified orthoptists evaluated adverse reactions using a questionnaire and interviewed the patients' guardians. The relationship between the adverse reaction rates and age, gender, additional instillation, complications of the central nervous system (CNS), time of day and season were analysed using binominal and polytomous logistic regression models. Results: The overall frequency of adverse reactions was 18.3% (118/646 patients). The main symptoms included conjunctival injection (10.5%, 68/646), drowsiness (6.8%, 44/646) and facial flush (2.2%, 14/646). The odds ratio (OR) of conjunctival injection increased with patient's age ( p < 0.05), in boys ( p < 0.01) and in winter ( p < 0.001). In contrast, the OR of drowsiness decreased with age ( p < 0.001). Facial flush was observed mostly in children younger than 4 years. CNS complications were not a significant risk factor for any of the symptoms. Conclusions: Adverse reactions to 1% cyclopentolate eye drops were more frequent than previously expected, but all were mild and transient. The probability of each symptom was associated with a clear age‐specific trend.